Efficacy of potentiation of performance through overweight implement throws on male and female high-school weight throwers - Judge, L. W.; Bellar, D.; Judge, M. (The Journal of Strength and Conditioning Research, 2010)
The purpose of the investigation was to determine the acute effects of heavy implements on weight throw performance. Ten high-school weight throwers were recruited to participate. A within-subjects design was used to compare the difference between mean and peak distances achieved with the regulation weight after warm-up with regulation weight (control), 1.37-kg overweight (OVRWGHT1) and 2.27-kg overweight implement (OVRWGHT2). Analysis via repeated-measures analysis of variance revealed main effects for Treatment (p = 0.021) and Attempt (p = 0.015). The mean after the OVRWGHT1 treatment was the highest (14.52 ± 3.54 m) followed by OVRWGHT2 (14.22 ± 3.15 m) and the competition weight implement (STAND; 13.38 ± 2.98). Paired samples t-test for peak distance by treatment revealed that both OVRWGHT1 (p = 0.004) and OVRWGHT2 (p = 0.027) were significantly different from STAND. Post hoc testing revealed that both OVRWGHT1 (p = 0.025) and OVRWGHT2 (p = 0.007) resulted in a significant difference in perceived fatigue compared with STAND. The results suggest that using overweight implements as part of the warm-up may improve performance in high-school athletes.